The Relationship Between Smoking and Poverty in Indonesia - Nur, Rasyidusman Hannamara Furqan (Dinasti Publisher, 2026)
This study aims to analyze the relationship between per capita cigarette expenditure and poverty levels in Indonesia based on the type of cigarette consumption. The method used is panel data analysis with the Common Effect Model (CEM) approach using data from 33 provinces during the 2019–2024 period sourced from the Central Statistics Agency (BPS). The dependent variable in this study is the poverty rate, while the independent variables include expenditure on cigarettes and tobacco (X₁), filtered kretek cigarettes (X₂), unfiltered kretek cigarettes (X₃), white cigarettes (X₄), tobacco (X₅), and other cigarettes and tobacco (X₆). The results show that simultaneously, all independent variables have a significant effect on poverty. Partially, unfiltered kretek cigarettes (X₃) have a positive and significant effect, indicating that increased consumption of this type worsens poverty conditions. Meanwhile, white cigarettes (X₄), tobacco (X₅), and other cigarettes and tobacco (X₆) have a negative and significant effect, indicating that these types are consumed more by people with high purchasing power. In general, cheap cigarettes consumed by low-income groups are a factor that exacerbates poverty.